2015
DOI: 10.2298/gensr1503131a
|View full text |Cite
|
Sign up to set email alerts
|

Using cytogenetic analysis RAPD in determination of genetic variations among four species of ornamental fishes of family: Poecilidae (Order: Cyprinodontiform)

Abstract: The karyological and molecular analysis of four fresh water fish species of Family: Poecilidae and their genetic relationships have been studied. Xiphophorus maculates and Xiphophorus hellerii have the same diploid chromosome number 2n=48, but they were different in their karyotypes. Poecilia sphenops and Poecilia reticulata have the same diploid chromosome number 2n=46 and the same fundamental number FN=46, also the same karyotype one group of acrocentric chromosomes. Nine RAPD primers, show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Several authors including (Santini et al, 2009;Sato and Nishida, 2010;Kai et al, 2011;Mazzuchelli et al, 2012;Guyomard et al, 2012;Schartl et al, 2013;Eschmeyer and Fong, 2014, Grassi, et al, 2017, Abu Almaaty et al, 2015& 2017aAlmeida, et al, 2017; reported that chromosome numbers confirm a large diversity in species of fishes in Class Actinopterygii which exhibit wide range , ranging from 2n=16 in ( Sphaerichthys osphromenoides ) to 2n=134 (Corydoras aeneus).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors including (Santini et al, 2009;Sato and Nishida, 2010;Kai et al, 2011;Mazzuchelli et al, 2012;Guyomard et al, 2012;Schartl et al, 2013;Eschmeyer and Fong, 2014, Grassi, et al, 2017, Abu Almaaty et al, 2015& 2017aAlmeida, et al, 2017; reported that chromosome numbers confirm a large diversity in species of fishes in Class Actinopterygii which exhibit wide range , ranging from 2n=16 in ( Sphaerichthys osphromenoides ) to 2n=134 (Corydoras aeneus).…”
Section: Discussionmentioning
confidence: 99%
“…The cytogenetic studies indicated that the diploid chromosome numbers of Actinopterygii ranging from 2n=16 to 2n =134 (Santini et al, 2009;Sato and Nishida, 2010;Kai et al, 2011;Mazzuchelli et al, 2012); Guyomard et al, 2012;Schartl et al, 2013;Eschmeyer and Fong, 2014;Grassi et al, 2017, Abu Almaaty et al, 2015& 2017aAlmeida et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies concluded that the diploid chromosome numbers of fishes ranging from 2n=16 to 2n =134. (Grassi et al, 2017, Abu Almaaty et al, 2015, 2017aAlmeida et al, 2017).…”
Section: Discussionmentioning
confidence: 99%